Price Equilibrium with Selling Constraints - José L. Moraga-González; Makoto Watanabe (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies how selling constraints, which refer to the inability of firms to attend to all the buyers who want to inspect their products, affect the equilibrium price and social welfare. We show that the price that maximizes social welfare is greater than the marginal cost. This is because with selling constraints, a higher price, despite reducing the probability of trade (fewer buyers are willing to pay a higher price) increases the value of trade (only trades generating positive surplus are consummated). We show that the equilibrium price is inefficiently high except in the limit when firms' selling constraints vanish and consumers observe prices before they visit firms. Thus, selling constraints constitute a source of market power.
Keywords: D40; J60; L10; L80; R30; 330; price competition; market power; capacity- and selling-constrained firms